Diagnostic performance of the AAP/EFP classification and the CDC/AAP case definition among pregnant women and a practical screening tool for maternal periodontal diseases - Li, Hui‐Jun; Zhao, Dan; Xu, Xiaoyi; Yu, Rong; Zhang, Feng; Cheng, Tianfan; Zheng, Zheng; Yang, Hong; Yang, Chuanzhong; Yao, Jilong; Wen, Ping; Jin, Lijian (Journal of periodontal research, 2022)
Background and Objective There is a limited number of studies on the performance assessment of the 2017 AAP/EFP classification and the CDC/AAP case definition among pregnant females. This study evaluated the agreement between these two systems and explored a practical tool for screening maternal periodontal diseases by general dentists. Materials and Methods Totally, 204 systemically healthy females at different phases of pregnancy underwent a full‐mouth periodontal examination. Demographic characteristics, lifestyles, and systemic conditions were recorded. Referring to the CDC/AAP definition, the diagnostic performance of the AAP/EFP classification was evaluated by the area under the ROC curve (AUC) and statistical tests (e.g., Youden's index and kappa coefficient). Additionally, a modified scoring system of the FDI Periodontal Diseases Chairside Guide (FDI‐CG) was formulated with the addition of pregnancy for testing accordingly. Results Overall, there were 22.1% of the participants in early phase of pregnancy (7–13 weeks) and 77.9% in late phase (34–36 weeks). The majority of them were below 35 years and non‐smokers without gestational diabetes. Notably, 30.9% of subjects presented with Moderate/Severe periodontitis (CDC/AAP), and 35.8% with Stages II‐IV periodontitis (AAP/EFP). Referring to the CDC/AAP definition, the AUC, Youden's index, and κ of the AAP/EFP classification were 0.979, 0.890, and 92.9%, respectively. The modified FDI‐CG system improved the AUC (0.815), Youden's index (63.0%), and κ (0.544) with reference to the original one. Conclusions This study shows that the AAP/EFP classification is in high agreement with the CDC/AAP definition among the pregnant women. The phases of pregnancy‐integrated FDI scoring system may serve as a convenient screening tool for maternal periodontal diseases in general dental practice.